STATISTICAL BLANKS AND QUESTIONNAIRES ON PRISONERS OF IRKUTSK PROVINCIAL PRISON IN 1920 - V. V. Ivanov; P. A. Novikov (Вестник Кемеровского государственного университета, 2015)
The paper is written on the basis of a rare type of sources: and statistical blanks and questionnaires prisoners of Irkutsk provincial prison in 1920, the analysis of the sources content allows understanding who became enemies of the Soviet government immediately after the defeat of the White movement.